Integrasi Model Hybrid TGfU-TPSR Net Games Terhadap Peningkatan Keterampilan Bermain dan Sikap Empati pada Anak Sekolah Dasar - Haifa Shafa Nabila; Dian Budiana; Gano Sumarno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to examine the effect of a hybrid Teaching Games for Understanding (TGfU) and Teaching Personal and Social Responsibility (TPSR) model in net games learning on elementary school students’ game performance and empathy. The study employed an experimental method using a One-Group Pretest–Posttest design. The participants were 32 sixth-grade students of SDN 113 Banjarsari selected through purposive sampling. Data were collected using the Game Performance Assessment Instrument (GPAI) to assess game performance and the Empathy Assessment Scale (EAS) to measure empathy. Data analysis was conducted using a Paired Sample t-test at a significance level of 0.05. The findings revealed that: (1) the implementation of the hybrid TGfU–TPSR model significantly improved students’ empathy; (2) the implementation of the hybrid TGfU–TPSR model significantly improved students’ game performance; (3) the integration of TGfU and TPSR effectively promotes game-related competencies while fostering students’ social-emotional development through game-centered learning and social responsibility experiences. Therefore, the hybrid TGfU–TPSR model can serve as an alternative physical education approach to support students’ holistic development in both psychomotor and affective domains. Keywords: Empathy, Hybrid TGfU–TPSR, Playing Skills, Net Games, Elementary School